IMPACT OF ANOMALIES ON FOOD PRICES IN TÜRKİYE - FETHI SABAN OZBEK (Journal of Animal and Plant Sciences, 2023)
Interest on building an early warning indicator to detect abnormal growth in prices in consumer markets has increased after the global food crisis of 2007/2008 and 2011. The indicator of food price anomalies (IFPA) identifies abnormally high or low prices that occur for a food commodity price series over a given period of time. This paper aims to present IFPA for selected products in Türkiye for the last ten years (2012-2021) in order to detect the anomalies in food prices through the quarterly and annual Compound Growth Rates (CGR), of the monthly price level. CGR is modified in order to account seasonality in this method. According to the results, abnormally high prices were measured in the years of 2013 and 2021 at most in Türkiye. And, no abnormally high prices were measured in the years of 2017 and 2019. Bread, veal, sunflower oil, milk, tea, wheat flour, fresh fish and olive were the food items abnormally high prices were measured more than one. Chicken meat, sunflower oil, milk, yoghurt and fresh fish were the food items abnormally high prices were measured in 2021. And, moderately high prices were measured for veal, egg and wheat flour in 2021. When the last three year situations of food items with abnormally high food prices were examined, it was observed that the abnormally high prices were intensively observed after COVID-19 pandemic started.
Keywords: Food Prices; Price Anomalies; Sustainable Development Goals; Türkiye